Epstein–Barr virus‐associated enteritis with multiple ulcers: The first autopsy case. Issue 11 (7th September 2020) - Watanabe, Hirofumi; Yamazaki, Yuto; Fujishima, Fumiyoshi; Ohashi, Yusuke; Imoto, Hirofumi; Sasano, Hironobu
Abstract : Epstein–Barr virus (EBV)‐associated enteritis is extremely rare and has not been well characterized. Herein, we present the first autopsy case of EBV‐associated enteritis with multiple ulcers in a 73‐year‐old Japanese male. The patient had abdominal pain and was clinically diagnosed with enteritis. An endoscopic examination revealed multiple ulcers at the terminal ileum. His condition worsened due to serosanguinous bowel discharge and the patient was then admitted to the hospital. Ileocecal and subtotal small intestinal resection was performed for repetitive hemorrhage from ulcers. However, the patient died due to uncontrolled hemorrhage. An autopsy was then performed in order to explore the cause of ulcers in the small intestine. Macroscopic findings revealed multiple ulcers with occasional cobblestone‐like appearance of the ileum. Histological analysis revealed marked infiltration of lymphocytes and plasma cells around the ulcer. EBV‐encoded RNA in situ hybridization (EBER‐ISH) revealed positive inflammatory cells. Cytomegalovirus was immunohistochemically negative. Macroscopic and microscopic findings obtained from autopsy specimens showed no foci of inflammation and EBER‐ISH‐positive stromal cells in the esophagus, stomach, and colorectum. EBV‐associated enteritis can cause uncontrolled repetitive hemorrhage from ulcers and result in critical condition of the patient, which can be used for differential diagnosis.